2021
DOI: 10.5539/ass.v17n11p39
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Leadership, Resilience, and Competence Amongst Police Officers in Klang Valley, Malaysia

Abstract: Excellent human resource development prioritizes organizational performance development elements. Organizational performance in Malaysia’s public sector is a concept that still needs to be explored. To date, improvements to leadership quality in order to enhance employee competence is one of the areas of study that has become the focus of researchers in the field of human resource development. In fact, leadership quality is also influenced by a person’s self-resilience to changes &ndash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Study also shown a high level of job performance among the police officers. This could be an impact of the various strategic plans implemented by PDRM to achieve optimum resilience and work performance (Razali et al, 2021), such as the Police Strategic Plan 2015-2020 and Police Integrity Plan 2016-2020. Police officers who are more resilient would have better morale, strength and dedication in improving their work performance (Giessing et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Study also shown a high level of job performance among the police officers. This could be an impact of the various strategic plans implemented by PDRM to achieve optimum resilience and work performance (Razali et al, 2021), such as the Police Strategic Plan 2015-2020 and Police Integrity Plan 2016-2020. Police officers who are more resilient would have better morale, strength and dedication in improving their work performance (Giessing et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As such, organizations with motivated employees are often more successful because employees will always find ways to perform their tasks effectively (De Jong & Den Hartog, 2007). Motivated employees also support the achievement of organizational goals because they will always find ways to improve their job performance (Razali et al, 2021).…”
Section: Hypotheses Of Studymentioning
confidence: 99%
“…The process of constantly improving and facilitating the development of human resource capabilities is called human resource development (Ainslie & Huffman, 2019;Bimenyimana, Abay, & Lee, 2021;Dirani et al, 2020;Edvardsen & Hoel, 2022;Goncharova & Zhidkova, 2021;Hamouche & Chabani, 2021;Koedijk, Renden, Oudejans, Kleygrewe, & Hutter, 2021;Kohlström, 2022;Kosmajadi, 2021;Mroziewski, 2021;Mukwevho & Bussin, 2021;Nascimento, Souza, & Adaid-Castro, 2020;Nasir, 2017;Parameswaran, 2020;Razali, Rami, Nazuri, & Suhaimi, 2021;Rothwell, Lindholm, Yarrish, & Zaballero, 2012;Staller & Körner, 2021;Sunahwati, Maarif, & Sukmawati, 2019;Tshukudu, 2021;Ulyanina, Levi, & Teplova, 2020). Human resource development itself is still considered by a number of scientists as part of human resource management (Armstrong & Taylor, 2014;Rothwell et al, 2012;Werner & DeSimone, 2012) although other scientists have viewed it as a new discipline (Tshukudu, 2021) with an interdisciplinary foundation (Jacobs, 1990).…”
Section: Introductionmentioning
confidence: 99%